Application of Sexing Technology in The Artificial Insemination Program and Cow Calf Operation - Kusuma Diwyanto; Herliantien . (Indonesian Center for Animal Research and Development, 2006)
In order to enhance cattle productivity and production, especially to support the cow calf operation, it is a need to have an application on innovative technology, such as spermatozoa sexing . Technology is more relevant nowadays due to the one of priority program in artificial insemination to increase genetic quality of cattle in Indonesia. Artificial Insemination Institute in Singosari had produced and commercialized thousands of straw with good results . The quality of frozen semen from those sexing sperm was very good, indicated with more than 40% rate of motility . By August 2006, 33 male calves out of 47 animals from the Y frozen semen (70 .2 1%) and 29 female calves out of 30 animals from the X frozen semen (96.66%) . The results shown that S/C reached 1 .71 and CR for 56.45% for its sexing frozen semen, which means these results are equal to the success of artificial program with unsexing frozen semen . Key words : Sexing technology, cow calf operation, artificial insemination